PIMA Handbook : Public Investment Management Assessment, 1st Edition. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2022)
This handbook is aimed at anyone who is involved in a Public Investment Management Assessment (PIMA) or who has a practical interest in public investment management. It is intended to be useful for country authorities, IMF staff, staff of other financial institutions and development organizations, and anyone who is interested in exploring different aspects of public investment management to understand how country systems are designed and how they work in practice.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Central Banks and Their Policies; Foreign Exchange; IMF Public Investment Management Assessment; Public Investment